Synaptic integration by NG2 cells - Sun, Wenjing; Dietrich, Dirk (Frontiers in Cellular Neuroscience, 2013)
NG2 expressing oligodendrocyte precursor cells stand out from other types of glial cells by receiving classical synaptic contacts from many neurons. This unconventional form of signaling between neurons and glial cells enables NG2 cells to receive information about the activity of presynaptic neurons with high temporal and spatial precision and has been postulated to be involved in activity-dependent myelination. While this still unproven concept is generally compelling, how NG2 cells may integrate synaptic input has hardly been addressed to date. Here we review the biophysical characteristics of synaptic currents and membrane properties of NG2 cells and discuss their capabilities to perform complex temporal and spatial signal integration and how this may be important for activity-dependent myelination.